1989
DOI: 10.1002/1097-0142(19890715)64:2<480::aid-cncr2820640222>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of serum TA-4 in monitoring patients with malignant transformation of ovarian mature cystic teratoma

Abstract: The development of cancer in mature cystic teratomas of the ovary is rare and sometimes difficult to detect because of sampling errors. Six cases of squamous cell carcinoma arising in ovarian mature cystic teratomas were studied, five of which showed an elevated level of a squamous cell carcinoma-associated antigen, TA-4, in the sera obtained preoperatively; the preoperative determination was not performed in the sixth case. However, no elevated TA-4 level was detected in the sera of 28 patients with mature cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Regarding tumor markers, squamous cell carcinoma (SCC) antigen seems to be the most useful tumor marker but from the evidences from many studies, it is still not sufficient to exclude malignant transformation preoperatively. However, in cases of recurrence, it has been shown to be useful because almost all reported cases have increased levels of SCC antigen, which usually preceded the clinical presentation by several months (Kimura et al, 1989;Tseng et al, 1996;Suzuki et al, 2000). Moreover, according to one previous study, approximately 60% of reported cases had a preoperative positive test result for CA125, and was found to be associated with poor prognosis and survival rates (Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tumor markers, squamous cell carcinoma (SCC) antigen seems to be the most useful tumor marker but from the evidences from many studies, it is still not sufficient to exclude malignant transformation preoperatively. However, in cases of recurrence, it has been shown to be useful because almost all reported cases have increased levels of SCC antigen, which usually preceded the clinical presentation by several months (Kimura et al, 1989;Tseng et al, 1996;Suzuki et al, 2000). Moreover, according to one previous study, approximately 60% of reported cases had a preoperative positive test result for CA125, and was found to be associated with poor prognosis and survival rates (Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical usefulness of tumor markers in patients with malignant transformation arising in MCT of the ovary is not clear (12) . However, like the serial SCC antigen is known as a useful tumor marker for SCC of the uterine cervix, SCC antigen also has been reported to be useful as a tumor marker for patients with SCC arising in MCT of the ovary (4,12–14) .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical usefulness of tumor markers in patients with malignant transformation arising in MCT of the ovary is not clear (12) . However, like the serial SCC antigen is known as a useful tumor marker for SCC of the uterine cervix, SCC antigen also has been reported to be useful as a tumor marker for patients with SCC arising in MCT of the ovary (4,12–14) . After Tseng et al reported that 16 of 24 (67%) patients with SCC arising in ovarian MCT had elevated SCC antigen levels and all patients with recurrent lesions had reelevated antigen levels in series SCC monitoring, they suggested that serum SCC antigen monitoring may be helpful in early detection of cancer recurrence (14) .…”
Section: Discussionmentioning
confidence: 99%
“…In stage I, when tumor was limited only to ovary, there were cases when adjuvant chemotherapy was given (16) and those which were just being observed and followed up (8,18) . In the more advanced stages, various treatments such as different chemotherapeutic regimens and/or radiation therapy were used with varied outcomes (1,5,(7)(8)(9)15,20,21) .…”
Section: Adjuvant Therapymentioning
confidence: 99%